2020
DOI: 10.1101/2020.05.13.093922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of repurposing drug candidates for the treatment of diseases caused by pathogenic free-living amoebae

Abstract: 33Diseases caused by pathogenic free-living amoebae include primary amoebic meningoencephalitis (Naegleria 34 fowleri), granulomatous amoebic encephalitis (Acanthamoeba spp.), Acanthamoeba keratitis, and Balamuthia amoebic 35 encephalitis (Balamuthia mandrillaris). Each of these are difficult to treat and have high morbidity and mortality rates 36 due to lack of effective therapeutics. In pursuit of repurposing drugs for chemotherapies, we conducted a high throughput 37 phenotypic screen of 12,000 compounds fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Although miltefosine has been reported to have moderate activity at concentrations of 63-100 µm 25,26 , another study 27 as well as ours suggest miltefosine activity may be less potent with a higher IC50 of >122 µm. As for pentamidine, our results are consistent with prior studies that obtained comparable IC50 values between 9 and 29 µm 24,28,29 . Thus, of the combination drug cocktail recommended by the CDC, only pentamidine and flucytosine appears to have in vitro activity against B. mandrillaris, though we were unable to test sulfadiazine.…”
Section: Phenotypic Screenssupporting
confidence: 92%
See 2 more Smart Citations
“…Although miltefosine has been reported to have moderate activity at concentrations of 63-100 µm 25,26 , another study 27 as well as ours suggest miltefosine activity may be less potent with a higher IC50 of >122 µm. As for pentamidine, our results are consistent with prior studies that obtained comparable IC50 values between 9 and 29 µm 24,28,29 . Thus, of the combination drug cocktail recommended by the CDC, only pentamidine and flucytosine appears to have in vitro activity against B. mandrillaris, though we were unable to test sulfadiazine.…”
Section: Phenotypic Screenssupporting
confidence: 92%
“…We therefore cannot rule out activity for the recommended drugs based solely on our in vitro sensitivity screens. We previously identified statins, which target 3-hydroxy-3-methylglutaryl-coenzyme A reductase A (HMG-CoA), as active compounds against B. mandrillaris 29 . As part of this study, we tested three additional statins: fluvastatin, atorvastatin and simvastatin and observed that they were active against B. mandrillaris at 1.18 to 3.03 µM concentration.…”
Section: Phenotypic Screensmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the epitome of neglected diseases with no major pharmaceutical companies and only a few academic labs working to discover new drugs. Phenotypic screening has significantly advanced the discovery and development of drugs targeting other parasitic protozoans and has been shown to be useful for the discovery of new drugs against pathogenic free-living amoebae as well [42][43][44]. In this study, we screened 400 bioactive compounds from the MMV Pandemic Response Box for activity against all three pathogenic free-living amoebae.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of 201 (50.25%) antibacterial compounds, 153 (38.25%) antiviral compounds, and 46 (11.5%) antifungal compounds. Previous high-throughput screening efforts on free-living amoebae have yielded promising leads for therapeutic development [40][41][42][43][44][45][46][47]. However, there is still a need for the discovery and development of novel chemical scaffolds potent against these amoebae.…”
Section: Introductionmentioning
confidence: 99%